A world of gesture culture and nonverbal communication - Archer, Dane; Silver, John (Berkeley, CA : Berkeley Media LLC, 2005)
Gestures from different cultures around the world are explored. People from many nations are shown performing all kinds of gestures and the different gestures that there are. Also explored are the meaning, function and origin of gestures.
Title from title screen.
Presenter: Dane Archer.
DVD format.
Keywords: Gesture; Nonverbal communication